Meta-Analysis of Postoperative Adjuvant Hepatic Artery Infusion Chemotherapy Versus Surgical Resection Alone for Hepatocellular Carcinoma - Ke, Qiao; Wang, Lei; Wu, Weimin; Huang, Xinhui; Li, Ling; Liu, Jingfeng; Guo, Wuhua (Frontiers in Oncology, 2021)
Background To systematically identify the long-term efficacy of postoperative adjuvant hepatic artery infusion chemotherapy (HAIC) for patients with hepatocellular carcinoma (HCC). Methods PubMed, MedLine, Embase, the Cochrane Library, and Web of Science were searched to collect the eligible studies up to March 31, 2021, that compared the surgical resection (SR) versus SR+HAIC for HCC patients. The endpoints were overall survival (OS) rates and disease-free survival (DFS) rates, and the effect size was determined by hazard ratio (HR) with 95% CI. Results A total of 12 studies (two randomized controlled trials (RCTs) and 10 non-RCTs) including 1,333 patients were eligible for this meta-analysis. The pooled results showed that OS and DFS rates in the SR+HAIC group were both better than those in the SR alone group (HR = 0.56, 95% CI = 0.41–0.77, p < 0.001; HR = 0.66, 95% CI = 0.55–0.78, p < 0.001, respectively). Furthermore, the subgroup analysis showed that patients would benefit from SR+HAIC regardless of chemotherapy regimens and courses (all p < 0.05), and patients with microvascular or macrovascular invasion would also benefit more from SR+HAIC in terms of OS and DFS (all p < 0.05). Conclusion Postoperative adjuvant HAIC could improve the long-term prognosis of HCC patients, especially for those with microvascular or macrovascular invasion, regardless of chemotherapy regimens and courses, but it deserves further validation.